Improving Aviation Safety in Indonesia: How Many More Accidents? - Nugraha, Ridha Aditya (Hasanuddin University, 2016)
Numerous and consecutive aircraft accidents combined with a consistent failure to meet international safety standards in Indonesia, namely from the International Civil Aviation Organization and the European Aviation Safety Agency have proven a nightmare for the countryâs aviation safety reputation. There is an urgent need for bureaucracy reform, harmonization of legislation, and especially ensuring legal enforcement, to bring Indonesian aviation safety back to world standards. The Indonesian Aviation Law of 2009 was enacted to reform the situation in Indonesia. The law has become the ground for drafting legal framework under decrees of the Minister of Transportation, which have allowed the government to perform follow-up actions such as establishing a single air navigation service provider and guaranteeing the independency of the Indonesian National Transportation Safety Committee. A comparison with Thailand is made to enrich the perspective. Finally, foreign aviation entities have a role to assist states, in this case Indonesia, in improving its aviation safety, considering the global nature of air travel.